Cryptogenic cirrhosis and Common variable immunodeficiency: an unrecognized relationship - Evcen, Recep; Bıyık, Murat; Çölkesen, Fatih; Sadi Aykan, Filiz; Kılınç, Mehmet; Gerek, Mehmet Emin; Akçal, Tacettin; Yıldız, Eray; Arslan, Şevket (The European Research Journal, 2025)
Objective: This study investigates the prevalence of Common Variable Immunodeficiency (CVID) in patients with cryptogenic cirrhosis. It aims to highlight CVID's role in liver involvement and raise awareness of its potential as an underlying cause of cryptogenic cirrhosis. Methods: This retrospective cohort study, approved by the ethics committee, included patients diagnosed with cryptogenic cirrhosis at a university hospital. Comprehensive evaluations were performed to exclude other causes of cirrhosis, and patients were screened for CVID based on the European Society for Immunodeficiencies (ESID) criteria. Results: This study included 30 patients with cryptogenic cirrhosis, among whom 6.7% (n=2) were diagnosed with CVID. Both CVID patients had low immunoglobulin levels and abnormal immune cell profiles, leading to recurrent infections in one case and suspicion due to low total protein levels in the other. IVIG treatment was initiated for both, and liver biopsy findings in one patient suggested CVID-related liver involvement. Conclusions: Determining the underlying causes of chronic liver diseases is crucial for guiding treatment and follow-up, potentially preventing cirrhosis progression and influencing liver transplantation eligibility. CVID screening in patients with cryptogenic cirrhosis should be considered, with appropriate treatments initiated as needed.